The Individualized Management Approach for Acute Poisoning - Muneera Al-Jelaify; Suliman AlHomidah (Advances in Pharmacological and Pharmaceutical Sciences)
Acute poisoning is a widespread emergency that mandates early management decisions for optimal outcomes. An individualized approach is an ideal way to provide those outcomes. Promoting awareness among healthcare professionals managing acute poisoning about the importance of incorporating the pharmacokinetics and following certain criteria to consider interventions such as activated charcoal, antidote, or specific investigations may improve their risk assessment strategies and management plans. To address the main aspects that should be considered to develop a customized poisoning management plan, we conducted this review based on relevant publications recovered by a careful search in PubMed. Our opinions as experts from the King Saud University (KSU) Drug and Poison Information Center (DPIC) were considered in the review.